Analysis of Physical Fitness of PGSD Study Program Students Class of 2022 Megarezky University - Muh Ilham Budi Utama; R Supardi; Budyanita Asrun (Indonesian Journal of Advanced Research, 2023)
This study aims to determine the state of the physical fitness level of the 2022 PGSD study program students. The variable in this study is the analysis of the physical fitness of the 2022 PGSD study program students at Megarezky University, while the sample of this study was 45 students consisting of 40 women and 5 men. Based on the results of the study it was found that the physical fitness of the 2022 PGSD study program students. The physical fitness of students on the test results. The average category is enough for 26 people (83%), Medium is 13 people (13%), and the Less category is 6 people (4%). By using the Indonesian Physical Fitness Test (TKJI) and data analysis that has been carried out, it is concluded that the Physical Fitness Analysis of PGSD Study Program Students Batch 2022, Megarezky University, is included in the good classification.